2004
DOI: 10.1029/2004gl020433
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological responses induced by the Tokachi‐oki earthquake in 2003 at hot spring wells in Hokkaido, Japan

Abstract: Thirty hydrological responses induced by the M8.0 Tokachi‐oki earthquake in 2003 were observed at hot spring wells and an undersea coal mine in Hokkaido, Japan. Most of the decreases and increases in groundwater levels or discharge rates can be explained as a poroelastic response to earthquake‐induced volumetric strain inferred from a fault model determined by dense static GPS observation. In five wells, observed groundwater‐level changes and inferred volumetric strain steps induced by the Tokachi‐oki earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Abrupt changes in well water levels in the nearfield (within 1-2 fault lengths) are often explained by the static poroelastic strain of aquifers caused by earthquakes (Akita and Matsumoto, 2004;Matsumoto and Roeloffs, 2003;Roeloffs and Bredehoeft, 1985;Shi et al, 2012;Shibata et al, 2010;Wakita, 1975;Wang and Chia, 2008;Zhang and Huang, 2011). In the intermediate and farfield (many fault lengths), the static poroelastic strains from displacement during earthquakes are small and can fail to explain the sign of the sustained variations in water levels .…”
Section: Introductionmentioning
confidence: 99%
“…Abrupt changes in well water levels in the nearfield (within 1-2 fault lengths) are often explained by the static poroelastic strain of aquifers caused by earthquakes (Akita and Matsumoto, 2004;Matsumoto and Roeloffs, 2003;Roeloffs and Bredehoeft, 1985;Shi et al, 2012;Shibata et al, 2010;Wakita, 1975;Wang and Chia, 2008;Zhang and Huang, 2011). In the intermediate and farfield (many fault lengths), the static poroelastic strains from displacement during earthquakes are small and can fail to explain the sign of the sustained variations in water levels .…”
Section: Introductionmentioning
confidence: 99%
“…The tidal effects in the well water level are primarily the responses to the volumetric strain of the aquifer in the subsurface, which are usually not subjected to interference by rainfall, discharge and other factors. Therefore, to some extent, we can study tide anomalies from well level observations prior to earthquakes without the influence of these sources of noise (Akita and Matsumoto, 2004;Li and Jiao, 2001;Riedel et al, 2010;Taniguchi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative evaluations of the relationship between the groundwater level and crustal static strain changes associated with earthquakes have been performed in recent years (Igarashi and Wakita, 1991;Quilty and Roeloffs, 1997;Koizumi et al, 2004). Akita and Matsumoto (2004) investigated coseismic groundwater level changes in a great many observation wells in Hokkaido, Japan induced by five earthquakes with M > 7.5 that occurred around the Hokkaido region. These researchers showed that groundwater level changes could generally be explained by coseismic static volumetric strain changes.…”
Section: Introductionmentioning
confidence: 99%